THE INFLUENCE OF SOCIAL MEDIA USAGE ON QUALITY TIME SPENT WITH FAMILY AMONG IIUM STUDENTS - Siti Hajar Mohd Badrol; Saodah Wok (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study was conducted to determine social media usage and its influence on the quality time spent with family among the students of the International Islamic University of Malaysia (IIUM). The objectives of the study are to determine: (a) the exposure to social media use; (b) the level of perception, attitude, and behavior towards social media use, and the quality time spent with family; and (c) the relationships of perception, attitude, and behaviour towards social media use with the quality time spent with family. Time displacement theory was used to explain the relationship between the variables. The quantitative research design was employed using a network sampling survey method, with a questionnaire as a tool for data collection. A total of 210 respondents participated in this study. The findings of the study revealed that WhatsApp is the most frequently used social media platform, followed by YouTube, E-mail, Instagram, Facebook, and Telegram. The levels of perception, attitude, and behavior towards social media usage and the quality of time spent with family are high and significant. Perception, attitude, and behavior were found to show a significant positive correlation with social media usage and the quality time spent with family. Thus, this study suggests that students should allocate the time they spend on social media for their families.